Um estudo sobre os livros de história da matemática para professores organizados pela sbhmat para os seminários nacionais de história da matemática - Rodrigues Junior, Antonio (2022)
The purpose of this dissertation is present a study about the books organized by the Brazilian Society of History of Mathematics for the mini-courses offered at the National Seminars on the History of Mathematics of the last twenty years. These texts, published biennially by educators and researchers, make up a collection designed for teachers, which aims to support them in their activities and which proves to be very effective for educational practices, at all levels, highlighting the importance of History for the teaching of Mathematics. Therefore, from research in references that deal with the potentialities of the History of Mathematics, observing some official documents for Basic Education, in particular, the National Common Curricular Bases and the Curricular Reference of Paraná, regarding the subject of Mathematics, objects of knowledge were systematically analyzed and highlighted in this collection, providing a panoramic view of the respective thematic units and their relative school years. The main objective was to analyze all the books produced, which total 121, released between 2001 and 2021, and, with that, to help teachers and students in the teaching and learning Mathematics process, providing a practical and useful record that can serve as a guidance instrument to find school contents related to the History of Mathematics in the listed texts, which can be worked with this methodology, both in Elementary and High School. Methodologically, a Bibliographic Research supports the data presented here. Regarding the results, they clearly highlight which subjects have some support material and, at the same time, make clear those that do not yet have them, so that, in due course, they can be prepared. With this, it is expected that the study can contribute both to students, in their learning, and to teachers, to teaching, when they know where to get reliable and quality supports, as well as to authors/researchers who are dedicated to producing these materials, showing them some gaps still to be completed, which makes this dissertation important for the area of Mathematics Education.